2022
DOI: 10.1108/arch-12-2021-0354
|View full text |Cite
|
Sign up to set email alerts
|

Courtyard configuration to optimize shading, daylight and ventilation in a tropical terrace house using simulation

Abstract: PurposeThis study aims to identify the optimal configuration to enhance the environmental conditions of a terrace house courtyard space in a hot and humid climate. The use of the courtyard has declined in new housing developments although it is an effective element to bring in light and wind to promote passive ventilation to occupants. To achieve the comfort level, the courtyard needs to be open, but some occupants modify it with enclosures, such as polycarbonate, to increase the useable and shaded area. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…To support this, many aspects should be considered in dwelling for providing the daylight level such as the shape and condition of windows, which have a significant influence on the interior daylight distribution and quantity [15] . Some research also demonstrated that the courtyards were mostly utilized in some traditional houses to provide indoor natural light [16][17][18] .…”
Section: Illuminance Standardmentioning
confidence: 99%
“…To support this, many aspects should be considered in dwelling for providing the daylight level such as the shape and condition of windows, which have a significant influence on the interior daylight distribution and quantity [15] . Some research also demonstrated that the courtyards were mostly utilized in some traditional houses to provide indoor natural light [16][17][18] .…”
Section: Illuminance Standardmentioning
confidence: 99%
“…Gunasagaran et al (8) conducted a simulation study to determine the optimal configuration for improving the environmental conditions of a courtyard space in a hot and humid climate. The study used a terrace house with a courtyard design in Penang as a case study.…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing simulations, the research examined the configurations of various courtyard terrace houses in Penang, Malaysia. Results indicated that a semi-enclosed courtyard with shading devices optimizes environmental conditions, contributing to the design of modern terrace houses in hot-humid climates [28].…”
Section: Introductionmentioning
confidence: 99%